The safety of single-physician procedural sedation in the emergency department. Issue 12 (27th November 2006) - Hogan, K; Sacchetti, A; Aman, L; Opiela, D
Abstract : Background: Pevious research has shown the safety of procedural sedation in the emergency department in university settings involving multiple emergency physicians. Objective: To examine sedation in the emergency department conducted by a single emergency physician with monitoring by the emergency nurse. Methods: The Procedural Sedation in the Community Emergency Department Registry is a prospective observational database of procedural sedation cases directed by the emergency physicians. Among other parameters, the registry tracts whether emergency physicians or emergency nurses monitored patient sedation. The incidence of complications and outcomes were compared between these two monitoring groups. Results: 1028 procedural sedations were performed on 977 patients at 14 sites. In 885 (86.1%) cases the emergency physician directed the sedation, and performed the procedure with monitoring by the emergency nurse. Complications occurred in 42 (4.1%) patients, 35 (4.0%) EN monitored patients and 6 (4.2%) EP monitored patients (p>0.7). Procedures were successful in 863 (97.5%) cases monitored by emergency nurses and in 140 (97.9%) patients monitored by emergency physicians (p>0.7). Conclusion: Procedural sedation in the emergency department performed by a single emergency physician is safe and effective.